Оценка личностных характеристик беременных в условиях санаторно-курортной реабилитации - Сюсюка, Володимир Григорович (My University, 2011)
On the basis of the study it is found that more than 30% of pregnant women are emotionally unstable, that should be considered in the individual approach in conducting medical and psychological correction of the contingent of women in sanatorium rehabilitation.
Keywords: тези